2021
DOI: 10.1167/jov.21.13.4
|View full text |Cite
|
Sign up to set email alerts
|

A general serial dependence among various facial traits: Evidence from Markov Chain and derivative of Gaussian

Abstract: The human vision system can extract a stable representation of the always-changing visual world. However, the mechanism underlying such perceptual continuity remains unclear. A possible candidate is the serial dependence: visual perception of an object is positively biased toward the visual input from the recent past. Does the visual system use one pattern of serial dependence for general purposes? Or different patterns of serial dependence for different visual tasks? Because different social facial traits (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…They named the bias as attractive serial dependence, which could help observers keep the temporal continuity of the physical environment. Such attractive serial dependence was also observed in other visual features, such as orientation ( Ceylan, Herzog, & Pascucci, 2021 ; Cicchini et al., 2017 ; Cicchini, Mikellidou, & Burr, 2018 ; Fischer & Whitney, 2014 ; Fritsche, Mostert, & de Lange, 2017 ; Pascucci et al., 2019 ; Samaha, Switzky, & Postle, 2019 ), spatial position ( Bliss, Sun, & D'Esposito, 2017 ; Manassi, Liberman, Kosovicheva, Zhang, & Whitney, 2018 ), expression, identity, and attractiveness of faces ( Kim, 2021 ; Liberman, Fischer, & Whitney, 2014 ; Taubert, Van der Berg, & Alais, 2016 ; Xia, Leib, & Whitney, 2016 ; Yu, Yang, & Ying, 2023 ; Yu & Ying, 2021 ), numerosity ( Kim, Burr, Cicchini, & Alais, 2020 ; Fornaciai & Park, 2018 ), and self-motion direction ( Wang et al., 2022 ; Xu et al., 2022 ). In contrast, some studies have found the opposite trend (i.e., repulsive serial dependence meaning that the perceived features of current trials are repelled away from the previously seen features, such as orientation) ( Alais, Leung, & Van der Burg, 2017 ; Kang & Choi, 2015 ; Bae & Luck, 2017 ).…”
Section: Introductionmentioning
confidence: 68%
“…They named the bias as attractive serial dependence, which could help observers keep the temporal continuity of the physical environment. Such attractive serial dependence was also observed in other visual features, such as orientation ( Ceylan, Herzog, & Pascucci, 2021 ; Cicchini et al., 2017 ; Cicchini, Mikellidou, & Burr, 2018 ; Fischer & Whitney, 2014 ; Fritsche, Mostert, & de Lange, 2017 ; Pascucci et al., 2019 ; Samaha, Switzky, & Postle, 2019 ), spatial position ( Bliss, Sun, & D'Esposito, 2017 ; Manassi, Liberman, Kosovicheva, Zhang, & Whitney, 2018 ), expression, identity, and attractiveness of faces ( Kim, 2021 ; Liberman, Fischer, & Whitney, 2014 ; Taubert, Van der Berg, & Alais, 2016 ; Xia, Leib, & Whitney, 2016 ; Yu, Yang, & Ying, 2023 ; Yu & Ying, 2021 ), numerosity ( Kim, Burr, Cicchini, & Alais, 2020 ; Fornaciai & Park, 2018 ), and self-motion direction ( Wang et al., 2022 ; Xu et al., 2022 ). In contrast, some studies have found the opposite trend (i.e., repulsive serial dependence meaning that the perceived features of current trials are repelled away from the previously seen features, such as orientation) ( Alais, Leung, & Van der Burg, 2017 ; Kang & Choi, 2015 ; Bae & Luck, 2017 ).…”
Section: Introductionmentioning
confidence: 68%
“…For instance, many researchers tested the influence of the previous perception on the current perception: the serial dependence (e.g., Taubert et al, 2016). This effect has been found in many facial perception tasks (e.g., Yu & Ying, 2021). Although it sounds unlikely, Yu et al (2023) using hidden Markov models suggested that the spatial and temporal influence the face perception in a complicated way.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 , 33 The models allowed precise projections into the future (Figure 3 ). 34 , 35 , 36 Additionally, the novel use of bootstrap simulations allowed for accurate quantification of the variance within these Markov chain projections (Figures 3 , 4 , 5 ). 37 , 38 , 39 , 40 Other studies that have attempted to quantify the variability present in Markov chain predictions focus on the transition matrix, with each transition probability having a confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The models allowed precise projections into the future (Figure 3). [34][35][36] Additionally, the novel use of bootstrap simulations allowed for accurate quantification of the variance within these Markov chain projections T A B L E 1 Summary of patient characteristics (demographic, socioeconomic, and laboratory measurements), stratified by individuals with weight loss versus no weight loss.…”
Section: Model Construction and Statistical Analysismentioning
confidence: 99%